An Ordinance Relating to Offenses and Disorderly Conduct and Repealing Ordinances no. 152, 178, & 471, Olympia City Council, Ordinance no. 523, § 2 (Washington, 1891). - (:unkn) unknown (General Publisher, 1891)
That any person who shall, within the limits of the City of Olympia, carry or wear under his clothes or concealed about his person, any pistol or pistols, dirk, dagger, slung-shot, cross-knuckles or any knuckles of lead, brass or other metal, bowie-knife, dirk-knife, razor or any other deadly or dangerous weapon, shall, upon conviction thereof before one of the police Justices of said city, be fined in any sum not to exceed twenty-five dollars, and default of the payment thereof, shall be committed to the city Jail until said fine and costs are paid, not to exceed ten days.
--
Keywords: CARRY - CONCEALED